Buddhist Architecture Exchanges between China and Pakistan - Wei, Lian (Pacific International Journal, 2023)
This study explores the friendly exchanges in Buddhist architecture between China and Pakistan from a geographical perspective. It probes mainly into the exchanges occurring from the 1st to the 10th century AD between ancient China and ancient Pakistan (the region where Pakistan is presently located). With the channels for exchanges between China and South Asia opening up and the Silk Road being established, the large-scale eastward spread of Buddhism became possible, creating opportunities for Buddhism communication between people of the two nations. The design and construction of Chinese Buddhist temples, pagodas and grottoes exhibit features typical of Buddhist architecture in ancient Pakistan, particularly the Gandhara Buddhist sculpture art that has profound influence on Buddha statues in China. In over a thousand years Chinese Buddhist architecture absorbed elements from that of ancient Pakistan, yet created its unique Chinese style, showing a perfect integration of the two cultures. The Buddhist architecture exchanges between ancient China and ancient Pakistan have far-reaching significance in promoting cultural communication and strengthening the friendship between people of the two nations.